The humility of holy fools in Orthodox Christianity: On the problem of understanding (The Vita of Simeon the Holy Fool and The Vita of Andrew the Holy Fool) - Dorofeeva L. (Слово.ру: балтийский акцент, 2014)
This article analyses the problem of understanding the deeds of a holy fool in Russian Orthodox culture. Through considering the images of two “classical” saints – Simeon the Holy Fool ad Andrew the Holy Fool, the author emphasises the idea of humility as the dominant type of behaviour and the main personal characteristic thus objecting to S.A.Ivanov’s concept of aggression as the key typological feature of holy fools. The article also analyses images of saint in the anthropological and axiological aspects, which makes it possible to explain the motivation of the “paradoxical” behaviour of holy fools and prove that the corresponding type of holiness relates to the ideas of boldness and humility as the ultimate form of self-denial.